Characterisation of the compositions and conditions of intrusions of late magma batches that contributed tothe Peninsula Pluton, Cape Granite Suite, South Africa - Christoffels, Casey Jade (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.